A survey on applying different control methods approach in building automation systems to obtain more energy efficiency - Behrooz, Farinaz; Ramli, Abdul Rahman; Samsudin, Khairulmizam (Academic Journals, 2011)
In this paper, the implementation of different control methodologies for controlling parameters of heating, ventilating and air-conditioning (HVAC) systems as a part of building automation systems were investigated. In the past few years, many researches have been done on application, structure and also efficiency of different methods to achieve saving more energy. Different control strategies were considered in terms of their advantages and disadvantages. In this research, fuzzy cognitive map (FCM) was recommended as a robust and simple method to decrease the energy consumption of HVAC systems. FCM is based on fuzzy logic and neural networks. FCM is a combination of the robust characteristics of these two methods. In this paper, the advantages of using FCMs have been indicated as a controller on the typical HVAC system among the other methods.